Finite element modelling and testing of filament-wound orthotropic components - Jones, Ivor Arthur (1993)
Existing software for CNC filament winding of fibre reinforced plastics has been linked to typical finite element codes by automating the generation of finite element models of filament wound components. The algorithms required for this process have been created and encoded as computer programs. The program FILFEM I generates models of components manufactured using the CADFIL I CAD/CAM system for the filament winding of axisymmetric components. The suite of programs named FILFEM II achieves the same objective for non-axisymmetric components manufactured using CADFIL II although its method of operation is quite different from that of FILFEM I. FILFEM I has been tested by automatically generating models of a pinched cylindrical filament-wound tube manufactured from glass-reinforced polyester resin. The results from these models generally compared well with results obtained from experiments and from an analytical solution extended by the author from work by Calladine. However, the validity of a comparison with experiment depends upon the accuracy of the material properties assumed in the analyses.